Do Lower-Carbohydrate Diets Increase Total Energy Expenditure? An Updated and Reanalyzed Meta-Analysis of 29 Controlled-Feeding Studies. Issue 3 (3rd December 2020) - Ludwig, David S; Dickinson, Stephanie L; Henschel, Beate; Ebbeling, Cara B; Allison, David B
ABSTRACT: Background: The effect of macronutrient composition on total energy expenditure (TEE) remains controversial, with divergent findings among studies. One source of heterogeneity may be study duration, as physiological adaptation to lower carbohydrate intake may require 2 to 3 wk. Objective: We tested the hypothesis that the effects of carbohydrate [expressed as % of energy intake (EI)] on TEE vary with time. Methods: The sample included trials from a previous meta-analysis and new trials identified in a PubMed search through 9 March 2020 comparing lower- and higher-carbohydrate diets, controlled for EI or body weight. Three reviewers independently extracted data and reconciled discrepancies. Effects on TEE were pooled using inverse-variance-weighted meta-analysis, with between-study heterogeneity assessed using the I 2 statistic. Meta-regression was used to quantify the influence of study duration, dichotomized at 2.5 wk. Results: The 29 trials ranged in duration from 1 to 140 d (median: 4 d) and included 617 participants. Difference in carbohydrate between intervention arms ranged from 8% to 77% EI (median: 30%). Compared with reported findings in the prior analysis ( I 2  = 32.2%), we found greater heterogeneity ( I 2  = 90.9% in the reanalysis, 81.6% in the updated analysis). Study duration modified the diet effect on TEE ( P  < 0.001). Among 23 shorter trials, TEE was reduced on lower-carbohydrate diets (−50.0 kcal/d; 95% CI: −77.4, −22.6 kcal/d) with substantial heterogeneity ( I 2  = 69.8). Among 6 longer trials, TEE was increased on low-carbohydrate diets (135.4 kcal/d; 95% CI: 72.0, 198.7 kcal/d) with low heterogeneity ( I 2  = 26.4). Expressed per 10% decrease in carbohydrate as %EI, the TEE effects in shorter and longer trials were −14.5 kcal/d and 50.4 kcal/d, respectively. Findings were materially unchanged in sensitivity analyses. Conclusions: Lower-carbohydrate diets transiently reduce TEE, with a larger increase after ∼2.5 wk. These findings highlight the importance of longer trials to understand chronic macronutrient effects and suggest a mechanism whereby lower-carbohydrate diets may facilitate weight loss.